Jacques Perriault et la formation à distance - Françoise Thibault (Centre National d'Enseignement à Distance, 2022)
Jacques Perriault is a famous French figure in the world of technology and educational media. This text aims to shed light on the valuable contribution his work made to research on distance education by favoring a dynamic approach to the profession of teacher-researcher. This work has benefited from developments by historians and sociologists of science who have studied the place and role of scientists and engineers in contemporary societies.